Ai-infused Immersion: Cultivating Efl Learners’ Intercultural Sensitivity Through Google’s Gemini Ai Chatbot - Sellami, Amina (The Journal of Studies in Language, Culture, and Society, 2025)
The pace of change in the 21st century is unprecedented. Some skills have fallen from favour while others have rapidly become obsolete. Intercultural sensitivity is among the needed competencies in this era. It guarantees effective intercultural communication in multicultural and plurilingual communities. Individuals with good levels of cultural awareness, empathy, openness, and sensitivity represent a highly desired social profile. Henceforth, this inquiry investigates the influence of using Google’s Gemini AI chatbot on cultivating EFL learners’ intercultural sensitivity. It follows a quasi-experimental mixed methods design with a single case study of 8 EFL third-year students from the University of Guelma, Algeria. The study contains a quasi-experiment which covered 8 sessions, 2 hours per each, in which 6 themes were covered. To measure learners’ intercultural sensitivity, Chen and Starosta’s (2000) intercultural sensitivity scale is adopted as a pre and posttest. The treatment also included a focus group discussion after completing the intervention. The quantitative analysis of the scale using the Wilcoxon signed-ranks test unveils a significant difference in pre and posttest results as learners excel from moderate to high level of intercultural sensitivity. The qualitative thematic analysis of focus group discussion reveals that learners developed their cultural knowledge, attitudes, and awareness, and became more ethnorelative. Thus, the findings support the alternative hypothesis which implies that the use of Gemini AI’s chatbot cultivates learners’ intercultural sensitivity. Eventually, this inquiry outlines a set of pedagogical recommendations for fostering intercultural sensitivity and AI integration in the Algerian EFL classroom.